Los niños y las niñas en la guerra: Respuestas desde el Derecho Internacional frente a los crímenes de reclutamiento de niñas y niños soldados y violencia sexual - Reyes Menéndez, Valeria (2017)
Around the world, the armed conflicts of recent years have been characterized by including the participation of child soldiers. Children, due to the vulnerability of their short age, suffer in a special manner of the war effects, and often their human rights are violated irreversibly. International Law has a duty to provide effective answers to tackle this situation, ensuring that children can be protected against those risks and that their rights can be guaranteed.